Advanced Project Management in Construction: Harnessing Tools and Techniques for Optimal Performance - Tisnawan, Rahmat; Husaini, Rizki Ramadhan; Hanifah, Mohd Hafizal (Tropical Scientific Journal, 2026)
Objective: This study conceptualizes Advanced Project Management (APM) as an integrated paradigm for enhancing construction project performance through the strategic convergence of digital technologies and adaptive managerial practices. Traditional project management approaches, often characterized by reactive decision-making and fragmented coordination, are increasingly inadequate for addressing the complexity, uncertainty, and digital transformation shaping contemporary construction projects. To bridge this gap, the study proposes a unified conceptual framework that aligns technological innovation with managerial excellence to achieve optimal project outcomes. Research Method: A systematic literature review was conducted using the Scopus database, focusing on peer-reviewed journal articles published between 2018 and 2025. From an initial pool of 175 publications identified through structured Boolean keyword searches, 23 studies were selected following screening and eligibility evaluation. The selected articles were analyzed through thematic coding across three analytical dimensions: (1) digital tools and technologies, (2) managerial techniques and strategic frameworks, and (3) project performance indicators. Findings: The synthesis reveals that APM represents a socio-technical ecosystem characterized by the integration of digital intelligence and managerial adaptability. Digital tools—including Building Information Modelling (BIM), Artificial Intelligence (AI), Internet of Things (IoT), and Digital Twin technologies—enhance transparency, predictive analytics, and real-time decision-making. Concurrently, managerial approaches such as Lean Construction, Agile Project Management, and Integrated Project Delivery (IPD) strengthen collaboration, flexibility, and continuous improvement. The interaction among these dimensions, reinforced through continuous feedback loops, contributes to measurable improvements in cost efficiency, schedule reliability, quality performance, sustainability, and organizational resilience. Originality: This study contributes a comprehensive conceptual framework that bridges digital transformation and strategic project governance within the construction context. By integrating technological and managerial perspectives into a unified model, the paper provides a theoretical foundation for future empirical validation using methods such as Structural Equation Modelling (SEM–PLS) or system dynamics modeling and offers practical guidance for organizations transitioning toward data-driven and adaptive project management systems